Aspects of the life and personality of R. C. Geary - Spencer, John E. (Economic & Social Studies, 1993)
Roy Geary, Ireland's greatest statistician, was born on 11 April 1896 in Dublin. His father attained as a boy a high place in UK civil service exams and began his career in the customs office in London but spent most of his subsequent career in the General Registrars Office in Charlemont House, now the Municipal Gallery, Dublin. His real talent was for statistics and he was associated with the Census of Population in 1901 (as clerk) in 1911 (in charge) and in 1926 (as advisor). As Roy was in charge of the Census in 1956, he laid claim to a family connection with all the Censuses from 1901 to 1956. Roy no doubt inherited a talent for statistics from his father (and also a love of soccer, his father being a founder member of Bohemians AFC).
Keywords: Statisticians; Biography; Economists; Ireland; R.C. Geary